Optimizing Marketing Strategies Optimizing Marketing Strategies for Gold Installment Products and Hajj Savings Case Study of BSI KCP Surabaya Klampis - Fianto, Aulia Zilvina Lauretta; Soviani, Enjeli Femi; Khoirudin, Faris; Salsabillah, Princess Diah (Majapahit Journal of Islamic Finance and Management, 2025)
This study aims to identify and optimize the marketing strategies for Gold Installment and Hajj Savings products at BSI Klampis Branch Office in Surabaya. Both products have significant potential to attract Muslim customers, but challenges in education, market segmentation, and marketing communications remain obstacles to increasing transaction volume. This study used a qualitative case study approach, conducted through in-depth interviews with BSI internal staff and direct field observations. The results indicate that the implemented marketing strategies include digital-based promotions, education through Islamic activities, and collaboration with local communities. However, the effectiveness of these strategies has not been maximized due to the lack of structured market needs mapping and low Islamic financial literacy among the target segment. Optimization of the strategy is recommended through strengthening digital channels, increasing the capacity of marketing staff, and developing an integrated literacy program. These findings are expected to provide strategic input for BSI in increasing market penetration for Gold Installment and Hajj Savings products sustainably in Surabaya and the surrounding area, as well as serve as a reference for other Islamic financial institutions in developing product marketing strategies based on Islamic values.